Improving Reading Literacy Strategy through Seven Programs of Reading Interest containing Da’wah Message - Abrori Abrori (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
The purpose of this study was (1) to describe the factors that cause low interest of students’ reading; (2) to describe the strategy to increase reading literacy through seven reading interest programs with preaching/ da’wah content at MTs Al Asror. The research method used was descriptive qualitative with literature literacy study. The results of the study showed that students are familiar with the 60 minute reading activity every morning. Selected reading material containing da'wah can shape the students’ characters that are polite, honest, obedient, and respectful and appreciative. In addition, the seven steps of the program which was done to improve students’ reading literacy are: (1) Library Management; (2) Seminars and Workshops; (3) 60 Minute Reading Movement every morning; (4) School Literacy Competition; (5) Book Review; (6) Literacy Award; and (7) The Book Exhibition. Those steps were proven to inspire, motivate, and attract students to read books.